Evaluation of psychiatric symptoms in patients diagnosed with fibromyalgia during COVID-19 pandemic: a cross-sectional study - Aşçıbaşı, Kadir; Özçete, Zeynep Alev (The European Research Journal, 2022)
Objectives: Our aim was to assess depression, anxiety, trauma symptoms and sleep problems in patients with fibromyalgia during the COVID-19 pandemic.Methods: This study was conducted face-to-face with 62 SARS-CoV-2 negative fibromyalgia patients. Sociodemographic and Clinical Data Form, Hospital Anxiety and Depression Scale (HADS), Pittsburgh Sleep Quality Index (PSQI), Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5), Coronavirus Anxiety Scale (CAS), Obsession with COVID-19 Scale (OCS), the American College of Rheumatology (ACR) Preliminary Diagnostic Criteria for Fibromyalgia 2010 were applied to the subjects. Results: Patient mean scores on the HAD Depression and HAD Anxiety scales were 8.42 ± 3.73 and 9.58 ± 3.86, respectively. The patients' PSQI and PCL-5 scores were 8.10 ± 3.49 and 33.90 ± 16.91, respectively. While the CAS score average was found to be 1.13 ± 2.79, the OCS score average was found to be 1.81 ± 2.27. The mean scores for the Widespread Pain Index (WPI), Symptom Severity Scale (SSS), and Visual Analog Scale (VAS) were 9.90 ± 3.03, 7.84 ± 2.07 and 7.37 ± 1.81, respectively. Poor sleep quality was identified in 75.8% and a risk of post-traumatic stress symptoms in 16.1%. SSS scores were found to be higher in those at risk of depression than those without (U=265, p = 0.003). OCS (U=256, p = 0.007), SSS (U=203.5, p = 0.001), VAS (U=263.5, p = 0.012), PCL-5 (U=144, p = 0.001) scores were found to be higher in those at risk of anxiety than those without. Conclusions: It was observed that depression was a predictor of fibromyalgia symptom severity and anxiety was a predictor of obsession with coronavirus, fibromyalgia symptom severity, VAS, and post-traumatic stress symptoms.